PERUBAHAN GAYA BERPAKAIAN ADAT KE PURA PADA MASYARAKAT HINDU DI DESA KERTA BUWANA KECAMATAN SUNGAI LOBAN KABUPATEN TANAH BUMBU - Sukarnasih, Ni Komang; Apriati, Yuli; P, Reski (Universitas Lambung Mangkurat, 2024)
Along with the development of the times, the traditional dress style for the temple has changed to become more modern, contemporary, following the trend. The aims of this study were (1) to find the factors causing changes in the traditional dress style to the temple in the Hindu community in Kerta Buwana Village (2) to find out the public's perception of the change in traditional dress style to the temple in the Hindu community in Kerta Buwana Village. The method used is a qualitative method, data sources selected by purposive sampling with 7 informants. Data collection was carried out by observation, interview, and documentation techniques. Data analysis was carried out by data reduction, presentation, and verification. Testing the validity of the data with extended observation and triangulation techniques, namely source triangulation, technical triangulation, and time triangulation. The results of this study indicate that: (1) Factors causing changes in traditional dress styles to Hindu community temples in Kerta Buwana Village, namely: (a) Internal factors due to the development of modifications to Balinese traditional clothing, and the desire to keep up with the times. (b) External factors, namely the influence of the surrounding environment, social media and online shops, one's economic condition. (2) The public's perception of changes in traditional dress styles to temples in the Hindu community in Kerta Buwana Village, namely the use of middle-aged traditional clothing for going to temples, changes in traditional dress styles are natural things that occur in modern times, the community accepts changes in traditional dress styles because there is no written rules governing the use of traditional clothing to temples, changes in traditional clothing have an unfavorable impact on the traditional dress style of the community, there are several things that are done to keep traditional clothing at temples consistent with ethics and standards taught such as socialization, obeying the directions given.